The Legal Position and Urgency of Postnuptial Agreements in the Perspective of Civil Law and Islamic Law - Febri Noor Hediati; Alimatu Mahfudhotin Kasanah; Yennita Astarina (Jurnal Independent, 2025)
Marriage, a fundamental human right, establishes a legal bond between a man and a woman, a bond that is recorded by the state in accordance with their respective religions and beliefs. Throughout the duration of a marital relationship, a variety of domestic issues may emerge. In recent times, domestic issues such as infidelity, online gambling, and domestic violence (DV) have become increasingly prevalent. The present study employs a doctrinal legal research method, utilizing both primary and secondary data sources. The primary sources consulted for this study include Law No. 1 of 1974, the Indonesian Civil Code (KUHPerdata), and the Compilation of Islamic Law. The secondary sources, which consist of supporting materials such as books, journals, and websites related to marital agreements, were also reviewed. The initial research finding indicates that, after the Constitutional Court Decision No. 69/PUU-XIII/2015, marital agreements can be executed not only prior to or concurrently with the initiation of marriage but also after the formal establishment of marital bonds. This signifies that postnuptial agreements are legally acknowledged and can be utilized to regulate the management of property and the responsibilities of spouses during marriage. A postnuptial agreement plays a crucial role in modifying legal provisions related to the separation of premarital property and inherited property within marriage. Marital agreements regulate wealth and may include additional clauses based on the principle of freedom of contract, if they do not contradict statutory law as specified in Article 1338(1) of the Civil Code. The second research finding indicates that the provisions of a postnuptial agreement offer numerous advantages under both positive law and the concept of maqasid al-syari’ah. These advantages include the protection of each spouse's assets, the prevention of financially detrimental actions, and the mitigation of the repercussions of domestic disputes.